Remote Ischemic Conditioning Improves Cognitive Function During Cerebral Vascular Injury Through the Induction of Autophagy - Wang, Hongjuan; Zhang, Qinglin; Xu, Yang; Bian, Hetao; Si, Cuiping; Yan, Zhongrui; Zhu, Meijia (Current Neurovascular Research, 2017)
Background: The most valid model for vascular cognitive impairment (VCI) is the mouse bilateral common carotid artery stenosis (BCAS), whose behavioral outcomes are supposedly affected by the remote ischemic conditioning (RIC) through the induction of autophgy. We hope to determine whether RIC contributes to the neuroprotection through the induction of autophagy. Methods: Wastar male mice were randomized into three groups including the Sham, the BCAS and the RIC+BCAS groups. All the animals were submitted to 4 cycles of 5 min occlusion and 5 min reperfusion of both the femoral vessels performing RIC. Then the animal behaviors were recorded as well as the expression of proteins and the mRNA levels. Notably, the expression of proteins relates to autophagy. By this means, it is possible to estimate the cell death, the severity of pathology and the expression of proteins under different groups. Results: Compared with the sham group, the expression of proteins increased for ATG7, Beclin-1, LC3, ATG5-ATG12 while decreased for P62 in the BCAS group. These changes were further promoted in the RIC+BCAS group, which indicates that the RIC can improve the cognitive function in the BCAS group. Moreover, RT-PCR demonstrated that the mRNA level of BECN1, Atg5, Atg7 in white matter (WM) and Hippocampus in BCAS group was higher than the sham group, while it was much greater in the RIC+BCAS group. This confirmed that the autophagy was activated in the BCAS and the RIC+BCAS groups, especially the RIC+BCAS group. Conclusion: Improved cognition during vascular injury and RIC was associated with increased activity of autophagy.
Keywords: BCAS